(untitled) (Fiep Bulletin - online, 2014)
The quality of life in the oldness interests all the professionals who believe that this phase of the life can be favored by emotional chances, physical and social. The present work had as study proposal to identify, between Hip Hop and Tango, which positively intervenes more with the states of moods of people in the Third Age. The research if characterizes for being a direct study, of qualitative form, demonstrating the result through pictures. It was analyzed objective by objective, comparing it enters the two styles of adopted dance and verifying which of the styles it was more positive. They had participated of the same group of the Third Age of Paranavaí-PR city, in a total of 27 people. 10 practical lessons had been carried through, where they had been separate for style, being first the five lessons of Hip Hop and the five last ones of Tango, where before, after the fifth lesson of Hip Hop and Tango was applied to the list of states of moods. The results found through the interference of the dance styles, had been seen and commented through the application of test LEA-RI, with 14 objectives, being 7 positives and 7 negatives. The test was applied before, and after the fifth lesson of the Hip Hop and the Tango, have been able to notice significant improvement in the moods states, mainly in the adjectives as negative, that they are: heavy / tired / loaded / sad / agitated / nervous / awkward / useless / indifference / shy and with fear, getting positive improvements and being Tango, the style most pleasant and positive for the Third Age.